2023
DOI: 10.3390/vaccines11020393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Negative Attitudes towards Vaccination in General and Trust in Government on Uptake of a Booster Dose of COVID-19 Vaccine and the Moderating Role of Psychological Reactance: An Observational Prospective Cohort Study in Hong Kong

Abstract: Uptake of a booster dose of COVID-19 vaccine is effective in preventing infection and severe consequences caused by COVID-19. The present study examined the effects of negative attitudes towards vaccination in general and trust in government on uptake of a COVID-19 booster dose, as well as the moderating role of psychological reactance to pro-vaccination messages in Hong Kong. An observational prospective cohort study using online survey was conducted among 264 adults. Findings showed that, after adjustment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…We observed that participants with "a lot of" trust in the government and "positive" perceptions regarding COVID-19 vaccines are more likely to accept the booster dose. These observations have similarly been reported in Hong Kong 51 and the United Kingdom. 52 Persons who have trust or confidence either in the government or in the vaccine itself are more likely to get vaccinated.…”
Section: Discussionsupporting
confidence: 88%
“…We observed that participants with "a lot of" trust in the government and "positive" perceptions regarding COVID-19 vaccines are more likely to accept the booster dose. These observations have similarly been reported in Hong Kong 51 and the United Kingdom. 52 Persons who have trust or confidence either in the government or in the vaccine itself are more likely to get vaccinated.…”
Section: Discussionsupporting
confidence: 88%